2013
DOI: 10.4236/ojas.2013.33030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prepartal oronasal administration of lipopolysaccharide on milk composition and productivity of transition Holstein dairy cows

Abstract: The aim of this study was to evaluate the effects of repeated oronasal administration of lipopolysaccharide (LPS) on milk composition and the overall productive performance of dairy cows. One hundred pregnant Holstein dairy cows were randomly assigned to two treatment groups (n = 50). 30 cows out of 100 were selected for intensive sampling (n = 15) starting at 28 d before parturition. Cows were administered orally and nasally with 2 and 1 mL of saline solution, respectively (control), or saline solution contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(43 reference statements)
1
0
0
Order By: Relevance
“…Shuster, Harmon, Jackson, and Hemken () also found a decline in milk fat content and lactational performance following intra‐mammary infusion with LPS. The milk protein content after challenge with LPS in our study was similar to the study by Iqbal, Zebeli, Mansmann, Dunn, and Ametaj (), which showed that protein content displayed a downtrend by oronasal LPS administration. Hinz, Larsen, Wellnitz, Bruckmaier, and Kelly () also demonstrated that exposure to LPS profoundly decreased milk protein content following infusion with LPS into the mammary gland.…”
Section: Discussionsupporting
confidence: 91%
“…Shuster, Harmon, Jackson, and Hemken () also found a decline in milk fat content and lactational performance following intra‐mammary infusion with LPS. The milk protein content after challenge with LPS in our study was similar to the study by Iqbal, Zebeli, Mansmann, Dunn, and Ametaj (), which showed that protein content displayed a downtrend by oronasal LPS administration. Hinz, Larsen, Wellnitz, Bruckmaier, and Kelly () also demonstrated that exposure to LPS profoundly decreased milk protein content following infusion with LPS into the mammary gland.…”
Section: Discussionsupporting
confidence: 91%